A brincadeira e o desenvolvimento psicomotor de crianças na Educação Infantil em uma Escola Pública no Distrito de Pedras - Barreirinha/AM - Santana, Maurício Paz (Brasil, 2023)
This article is the result of concerns about the psychomotricity development process, through games and play in Early Childhood Education, important practices for teaching and learning. It aimed to analyze how play develops the child's psychomotricity in Early Childhood Education in a rural school. Playing with a view to the development of psychomotricity helps the child to excel in physical activities, allowing physical, cognitive, affective development, in addition to socialization with classmates and the basic principles of rules of conduct. This article is based on studies by Vygotsky (1991), Almeida (2019), Fonseca (2008), Kishimoto (2005). The study has a qualitative and descriptive approach based on observation and an interview with a teacher at a rural school in the municipality of Barreirinha-AM. The results state that psychomotor development stimulates the child's learning process, as games are an important form of communication between children, it is through these that children produce knowledge, develop reasoning skills, autonomy and creativity. It is concluded that there is a greater participation of children in traditional games, and the teacher has the necessary knowledge to work with the ludic, in which it is a facilitating development at the time of learning, such as, for example, personal, social and cultural development, however to Quality and enjoyable learning requires a suitable environment for innovative activities and resource materials in the countryside school.